Fiber Analisis Redaman Jaringan FTTH Berbasis GPON Pada CV. Vyasti Network Di Luar Batang Jakarta Utara - Reynaldi, Reza; Syamsu, Muhajir; Diana Yusuf (Jurnal Teknologi Informasi (JUTECH), 2024)
Fiber to the Home (FTTH) is a network technology that provides high-speed internet connectivity directly to homes. FTTH has revolutionized the world of internet communication by using optical fiber as the main transmission medium, providing superior speed and signal quality. Fiber To The Home has also developed the multimedia industry, as FTTH can provide multimedia services. Fiber To The Home utilizes GPON (Gigabit Passive Optical Network) technology to save time in processing the delivery of various data and communication information. This research aims to analyze the acceptable limits of network attenuation in Fiber To The Home (FTTH), to address attenuation values that exceed the predetermined acceptable limits and to identify the causes of increased attenuation in the network. The method used in this research is the NDLC (Network Development Life Cycle) method and the method that analyzes the attenuation value of each core in the PON that has been determined. The attenuation values must comply with the predetermined acceptable limit of -28 dB. The causes of increased attenuation are the presence of connections on each cable, the number of cables leading to one distribution point, and bends in the cable exceeding 45°. To address attenuation values that exceed the acceptable limit, management of the core in fiber optic cables is conducted, reducing the potential for increases in attenuation values that exceed the acceptable limits